δ-endotoxin activity and spore production in batch and fed-batch cultures of Bacillus thuringiensis - Avignone Rossa, Claudio Adolfo (1993)
The toxicity and the spore count of batch and fed batch cultures of Bacillus thuringiensis var. israelensis were studied. Spore counts reached in both batch and fed batch cultures were as high as those reported in the literature, but the levels of toxicity found in the latter were about one order of magnitude lower than those attained in batch cultures. Avoiding restricted cultures might be necessary to reach high titres of δ-endotoxin, which are essential if a good product is intended. Furthermore, spore count might not be a good parameter to predict insecticidal activity of Bacillus thuringiensis cultures.